Management of Idiopathic Macular Telangiectasia Type 2 - Alireza Khodabande; Ramak Roohipoor; Javad Zamani; Masoud Mirghorbani; Hamidreza Zolfaghari; Shahab Karami; Bobeck S. Modjtahedi (Ophthalmology and Therapy, 2019)
Abstract Macular telangiectasia type 2 (MacTel) is a relatively rare disease without established treatments. Although MacTel was previously considered a primarily vascular condition, the thinking on its pathogenesis has shifted to it now being considered principally a neurodegenerative disease. This has resulted in a subsequent change in the approach to treatment toward neuro-protection for the non-proliferative phase of this disease. Carotenoid supplementation has had mixed results. Ciliary neurotrophic factor (CNTF) has demonstrated some promising early results, but further study is necessary to determine its actual effect. Some structural improvements have been seen in the non-proliferative phase with oral acetazolamide but without accompanying functional improvement. Anti-vascular endothelial drugs have been studied and not found to have benefit in the non-proliferative phase of disease but have demonstrated significant structural and functional value in the treatment of secondary neovascularization. There is no level I evidence for the various proposed MacTel treatments, and efforts need to be directed toward conducting multicenter randomized trials to better understand possible treatments for this condition.